Large-scale RNAi screens to dissect TNF and NF-κB signaling pathways - Oliver Metzig, Marie; Nickles, Dorothee; Boutros, Michael (Advances in TNF Family Research, 2011)
TNFR signaling and activation of NF-κB plays a central role in balancing tissue homeostasis. Aberrant regulation of this signaling pathway contributes to many human diseases, including cancer, neurodegeneration, and pathogenic infections. Much effort is currently spent on investigations to understand its regulation and to define new targets for therapeutic interventions. In this chapter, we review large-scale RNAi screening approaches as a powerful tool for the dissection of signaling pathways. Using the example of a recently performed screen for novel regulators of TNFα/NF-κB signaling among the family of human deubiquitinating enzymes (DUBs), we summarize requirements for setting up a screen and the follow-up of candidate genes. In conclusion we give an overview about current therapeutic options targeting TNFα signaling and discuss the relevance of target discovery by RNAi for progress in cancer therapy.
First Online: 22 October 2010
Gesehen am 18.08.2022